Examining the association between diet-related situational factor and dietary behavior: an observational study of diet-related situational factors in stroke patients during rehabilitation - Zhong, Weiying; Pan, Xi; Li, Jiaxuan; Zhang, Yi; Chen, Lei; Sun, Xueqi; Wang, Zhi; Xu, Lan (Frontiers in Nutrition, 2025)
BackgroundDietary behavior is affected by various factors and adverse dietary behavior is a risk factor for stroke recurrence. The current study examined the relationship between dietary behavior and relevant situational factors in stroke patients during rehabilitation.MethodsA total of 257 stroke patients recorded dietary intake and assessed diet-related situational factors at each meal via an information platform for three consecutive days during rehabilitation. A multiple logistic model was developed to analyze how diet-related situational factors influence dietary behavior.ResultsA total of 183 participants completed the study. Lunch accounted for the highest proportion (44.5%) of energy-qualified meals and breakfast for the lowest proportion (37.8%). Patients with a noisy dining environment, who needed help from others to cook or shop for groceries independently or who ate in a public open space were more likely to have adverse dietary behavior at breakfast. Patients who had a noisy dining environment, who needed help from others to cook or shop for groceries or who ate with friends were more likely to have adverse dietary behavior at lunch. Patients in the early stages of recovery, who had a noisy dining environment, who needed help from others to cook or shop for groceries, who ate with friends and had a high level of satisfaction with eating were more likely to show adverse dietary behavior at dinner.ConclusionPoor dietary behavior was common in stroke patients with low probability of qualified energy intake during rehabilitation. Meal location and companions were among the situational factors that influenced dietary behavior.